Effect of a Gamified Web-Based Literature Review Platform on Creative Engagement and Research Self-Efficacy Among Graduate Students - Dwi Valinia Ivanka; Dian Rahayu (Enigma in Education, 2026)
Nations and universities increasingly recognize the literature review as a core graduate research competency, yet students often experience it as tedious and demotivating. This study investigated the effect of a gamified web-based literature review platform on creative engagement and research self-efficacy among graduate students. The study aimed to test whether gamification enhances graduate research competency. A quasi-experimental pretest–posttest control group design was employed involving 78 graduate students in research methodology courses at a public university in Palembang, Indonesia, during the 2023/2024 academic year. An intervention group (n = 39) used a platform incorporating points, badges, leaderboards, and challenge-based tasks, while a control group (n = 39) used traditional methods over 12 weeks; all scores were expressed on a 0–100 metric. Analysis of covariance with pre-test covariates showed that the intervention group scored significantly higher in creative engagement (74.6 vs 56.2, p < 0.001, d = 1.42), research self-efficacy (69.2 vs 53.1, p < 0.001, d = 1.28), intrinsic motivation (72.8 vs 58.3, p < 0.001, d = 1.15), and literature review quality (68.4 vs 51.7, p < 0.001, d = 1.34), with effects robust after Bonferroni correction. The findings indicate that gamified web-based platforms are an effective pedagogical innovation for the literature review process.